Hand- och benstyrka vid intensivvårdsavdelning (IVA)-mottagning, -en retrospektiiv studie - Eliasson, Sara; Wanecek, Michael; Block, Tomas (Nordisk Tidsskrift for Helseforskning, 2020)
Strength in hand and legs at intensive care unit (ICU) follow up-reception: a retrospective study Early mobilization is well established in intensive care and includes sitting, standing and walking and thereby lower extremity activation. Equivalent strategy for upper extremity activation is lacking, therefore, there might be a higher degree of remaining disability in the hand/arm. This retrospective study aimed to describe the strength in hand and legs, and the relationship therebetween, at an intensive care unit (ICU) follow up-reception. Hand dynamometer and Timed-Stands Test (TST) were measured and correlated to illness severity by Simplified Acute Physiology Score III (SAPS3). Data from 47 participants was compared to matched control values. The hand strength was lower (p=0,028) with low effect (r=-0,2), of clinical relevance as it may affect the ability in activities of daily living (ADL). There were no significant differences for strength in the legs, correlation between strength and illness severity and for comparison of strength divided by illness severity. Larger studies are recommended.